2013
DOI: 10.3390/en6105046
|View full text |Cite
|
Sign up to set email alerts
|

Operating Point Optimization of a Hydrogen Fueled Hybrid Solid Oxide Fuel Cell-Steam Turbine (SOFC-ST) Plant

Abstract: This paper presents a hydrogen powered hybrid solid oxide fuel cell-steam turbine (SOFC-ST) system and studies its optimal operating conditions. This type of installation can be very appropriate to complement the intermittent generation of renewable energies, such as wind generation. A dynamic model of an alternative hybrid SOFC-ST configuration that is especially suited to work with hydrogen is developed. The proposed system recuperates the waste heat of the high temperature fuel cell, to feed a bottoming cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Some researchers are trying to develop the high energy density power source which could be changed through various approaches [9]. Several models for operating conditions were proposed to reach the maximal efficiency of the SOFC system [10]. The design and optimization of SOFCs were conducted to understand the relationship between the parameters and performance when using the numerical model [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers are trying to develop the high energy density power source which could be changed through various approaches [9]. Several models for operating conditions were proposed to reach the maximal efficiency of the SOFC system [10]. The design and optimization of SOFCs were conducted to understand the relationship between the parameters and performance when using the numerical model [11].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the equations used in the modeling for calculating the maximum voltage achievable by the solid oxide fuel cell are: (11) where V N represent the Nerts voltage and V Loss stands for the voltage losses. It is important to recall that after a SOFC delivers electrical current, its components exhibit a resistance which results in voltage losses.…”
Section: Application Of Exergy 70mentioning
confidence: 99%
“…Furthermore, developments of hybrid systems are being expanded to run other power generation systems as trigeneration systems [8,9], steam turbines [10,11] and gasification [12]. In this context, a comparative energy and exergy analysis of an SOFC/GT waste heat to power conversion employing Kalina and Organic Rankine cycles is reported [13].…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that the efficiency is increased by 14% -25% by recovering SOFC waste heat through ORC based on investigated design parameter conditions. Ugartemendia et al [8] developed a dynamic model of an alternative hybrid SOFC-ST configuration and showed that maximum efficiency is obtained when the utilization factor is 0.65 at a temperature of 900˚C for a 120 kW rated SOFC.…”
Section: Introductionmentioning
confidence: 99%